Revolutionizing Religious Advocacy: Unleashing The Potential Of Digital Da'wah And Its Boundaries For Muslim Women Activists - Raihana, Siti Nazla; Fristyarini, Annisa (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
Every Muslim has an obligation to preach to spread the word of Islam. Da’wah activities are currently dominated by male activists, even though women also have the same obligation to preach, in fact there are matters that women know better, especially those related to feminine issues. Therefore, women are required to preach by paying attention to the limits set by the Sharia. As exemplified by the ummahatul mu’minin and other shahabiyat during the heyday of Islam where they took an active role in spreading the teachings of Islam by forming hadith halaqah and other learning media. This research aims to explore how the contribution of da’wah of Muslim women activists in the digital era 5.0 and the limits set by Islam. The method used in this research is a qualitative approach with data analysis method. The results of this study indicate based on the takhrij hadith of the Prophet ﷺ that Muslim women da’wah activists can spread Islam through social media, by maintaining restrictions such as: maintaining aurat and voice, not being tabarruj, not mixing with men, not promoting heretical thoughts, preaching according to their abilities and fields, preaching politely, and also setting an example by practicing what is preached. So it can be concluded that in the digital era 5.0 there are many ways for Muslim women to contribute to spreading Islam, Islam gives full support to Muslim activists who preach according to the corridors of Islam.